The Improbable Success of the Petit-Poitou Company, 1650-1720: Agency and Management at the Crossroads of Social and Environmental History - Kennedy, Gregory (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l’Université Laval, 2015)
The Petit-Poitou Company stands out as the first successful large-scale drainage enterprise in France. Created in 1640 by a group of local officials and landowners, by 1646 the Company had completed the operation of draining nearly 4,000 hectares of marshland for farming. This article examines the seventy years following this initial success in order to better understand how the Company overcame significant environmental, social, and political challenges to emerge as a stable and profitable enterprise. This success was highly improbable. Flood disasters, dissension amongst the associates, the actions of tenant farmers, and challenges from regional competitors all threatened to destroy its work. But the Company was able to learn from its early mistakes, build consensus internally, and defend itself from the legal attacks of its rivals through a flexible but firm leadership model and a solid understanding of territorial management and court patronage. This article is based on original research using the unique and previously little-known records of the General Assembly of the Petit-Poitou Company and proposes a more comprehensive view of this period of development for the Company. In other words, it offers a microhistorical analysis that can add to current debate about human agency in the environmental and social history fields.